2015
DOI: 10.1097/lgt.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vaginal Lubrication on Unsatisfactory Results of Cervical Smears

Abstract: It seems that speculum lubrication does not interfere with the rates of unsatisfactory results when examination is based on conventional cytology. Conversely, however, the limited number of studies evaluating speculum lubrication on liquid-based cytology precludes firm conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…In a recent research aimed at investigating the effects of a lubricated speculum on pain, Uygur et al have shown that a small amount of lubricant in the examination speculum would not interfere in the quality of cytology results. That study has also cited other authors, reporting that the use of water‐based lubricant did not alter the rates of unsatisfactory results. In contrast, other studies have shown higher rates of unsatisfactory samples, because of lubricant use during the examination .…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…In a recent research aimed at investigating the effects of a lubricated speculum on pain, Uygur et al have shown that a small amount of lubricant in the examination speculum would not interfere in the quality of cytology results. That study has also cited other authors, reporting that the use of water‐based lubricant did not alter the rates of unsatisfactory results. In contrast, other studies have shown higher rates of unsatisfactory samples, because of lubricant use during the examination .…”
Section: Discussionsupporting
confidence: 71%
“…Other studies have also shown a decrease in pain when using a lubricated speculum without interfering with Pap smear quality. Such results encourages practitioners to use lubricant for the examination, without changing the sample results …”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations